Interaction of inferior temporal cortex with frontal cortex and basal forebrain: double dissociation in strategy implementation and associative learning. - Gaffan, D; Easton, A; Parker, A (2002)
Macaque monkeys learned a strategy task in which two groups of visual objects needed to be treated differently, one with persistent and one with sporadic object choices, to obtain food rewards. After preoperative training, they were divided into two surgical groups of three monkeys each. One group received crossed unilateral removals of frontal cortex and inferior temporal cortex (IT x FC) and were severely impaired in performing the strategy task. The other group received bilateral transection of anterior temporal stem, amygdala, and fornix (TS+AM+FX) and were unimpaired in performing the strategy task. Subsequently the same animals were tested in visual object-reward association learning. Here, confirming previous results, group IT x FC was unimpaired, whereas group TS+AM+FX was severely impaired. The results show that the amnesic effects of TS+AM+FX cannot be generally attributed to the partial temporal-frontal disconnection that this lesion creates, and therefore support the hypothesis that the amnesic effects of this lesion are caused primarily by the disconnection of temporal cortex from ascending inputs from the basal forebrain. The results also show that temporal-frontal interaction in strategy implementation does not require those routes of temporal-frontal interaction that are interrupted in TS+AM+FX, and therefore support the hypothesis that projections to other posterior cortical areas allow temporal and frontal cortex to interact with each other by multisynaptic corticocortical routes in strategy implementation.